2004
DOI: 10.1111/j.1365-2982.2004.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric distension alters frequency and regularity but not amplitude of the gastric slow wave

Abstract: The aim of this study was to assess effects of gastric distension on gastric slow waves using internal and cutaneous electrodes and the correlation between these two measurements. The study was performed in five dogs implanted with one pair of serosal electrodes and a gastric cannula. Gastric slow waves were recorded using both cutaneous and internal electrodes in several sessions with different volumes (150-600 mL) of gastric distension with a barostat balloon. Bethanechol was injected in one of sessions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…Food‐induced slowing of SWR is also likely to be multifactorial in origin. Previous studies have shown that gastric distension diminishes SWR, 4 in a volume‐dependent manner 17,18 . As with impedance, we observed that changes in SWR were correlated with balloon volume, but significantly diminished only with the largest volume.…”
Section: Discussionsupporting
confidence: 75%
“…Food‐induced slowing of SWR is also likely to be multifactorial in origin. Previous studies have shown that gastric distension diminishes SWR, 4 in a volume‐dependent manner 17,18 . As with impedance, we observed that changes in SWR were correlated with balloon volume, but significantly diminished only with the largest volume.…”
Section: Discussionsupporting
confidence: 75%
“…This result provides further evidence that the MGG and EGG record different phenomena than intraluminal manometry. It remains unclear to what extent the postprandial amplitude increases can be ascribed to gastric distension as opposed to an actual increase in gastric activity, but other authors have addressed this question 10,45,46 . The consensus appears to be that postprandial signal power increases may or may not correspond to actual increases in slow wave activity, but postprandial amplitude decreases are generally considered pathological 47 .…”
Section: Discussionmentioning
confidence: 99%
“…These issues have led some to suggest that temporal characteristics of the EGG signal such as slow wave frequency are the only potentially reliable information obtainable from cutaneous recordings 5–9 . Postprandial increases in EGG power may be attributed to either increased motility or decreased source‐to‐electrode separation caused by gastric distension; however, it is not currently possible to determine the relative degree each factor contributes to the increased power 10 . A recent study by Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric contractility is closely coupled to the mechanosensitivity located in the gastric wall [12, 23, 24]. The myogenic response of the gastric smooth muscle and efferent neurogenic contraction are regulated by mechanoreceptors: afferent and efferent vagus nerves [1, 6, 9, 11, 12, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…The myogenic response of the gastric smooth muscle and efferent neurogenic contraction are regulated by mechanoreceptors: afferent and efferent vagus nerves [1, 6, 9, 11, 12, 23, 24]. The relation between afferent vagus signals and gastric distension was identified decades ago [6, 9, 11, 12].…”
Section: Discussionmentioning
confidence: 99%